Russia : Issues in Public Expenditure Policy - Morozov, Alexander; Sundberg, Mark W. (World Bank, Washington, DC, 2013)
This note briefly outlines key public expenditure policy issues facing Russia today. Dramatic changes have taken place on the public expenditure landscape since the start of transition. In the first year after the dissolution of the Soviet Union, total recorded public expenditures captured over two-thirds of total Gross Domestic Product (GDP). Within the next two years this was reduced to 46 percent of GDP, and by 1998 consolidated budget and extra-budgetary recorded expenditures reached an estimated 39 percent of GDP.